Long-term iron supplementation in four patients with X-linked erythropoietic protoporphyria: associations with serum proteins and erythrocyte protoporphyrin levels—a single-centre retrospective study - Minder, Anna-Elisabeth; Granata, Francesca; van Breemen, Franziska; Schneider-Yin, Xiaoye; Minder, Elisabeth I.; Saleh, Lanja; Barman-Aksözen, Jasmin (Frontiers in Molecular Biosciences, 2025)
IntroductionX-linked erythropoietic protoporphyria (XLEPP) is an ultra-rare inborn error of the heme biosynthesis characterised by the accumulation of large amounts of protoporphyrin IX (PPIX) and zinc-protoporphyrin in the erythrocytes. PPIX absorbs the energy of the visible light range and upon exposure causes painful phototoxic reactions and tissue damage. In addition, PPIX is excreted via the liver and bile, and can induce liver failure that requires life-saving liver transplantation. Case reports and data from a limited number of patients enrolled in a prospective study indicate that supplementation with iron, a co-substrate of the heme biosynthesis, can decrease blood PPIX concentrations and improve liver damage and photosensitivity in patients with XLEPP. However, long-term data on safety and effectiveness of iron supplementation in XLEPP to support this treatment strategy is limited.MethodeHere, we report the experience and long-term effects over up to 8 years of iron supplementation of the four patients with XLEPP in the Swiss cohort.ResultsOur study shows that iron supplementation was safe and effective in lowering blood PPIX concentrations in our patients in the long term.DiscussionHowever, monitoring for adequate dosing and long-term effects is advisable and a standardisation of treatment protocols and international best practice guidelines are needed.